The role of social networking sites in shaping Saudi public opinion towards women officiating leadership positions “Twitter as a model” - A field study - Saudi Arabia - Alotaibi, Nouf Khalid (Journal of Humanities & Social Sciences, 2021)
The study aimed to measure the extent of the influence of opinions on social media sites (Twitter as a model) on shaping the direction of Saudi public opinion, towards Saudi women assuming leadership positions. Also, monitoring the extent of social interest and the importance of awareness of the axes of the vision of women among the Saudi public. This study analyzes the role of some (demographic) factors In shaping the trend towards Saudi women assuming leadership positions, knowing the opinions circulating on social media sites (Twitter) about what are the obstacles that hinder Saudi women assuming leadership positions. The researcher followed the social survey approach. The study sample was chosen randomly from those who use social media sites in the community The Saudi study sample amounted to (300) female members of both sexes and their ages ranged between (18-65 years). The questionnaire was distributed to them and the data was collected and analyzed. The study reached several results: 1- The average time the study sample spends on social media per day is 4-6 hours per day. 2- Twitter is one of the favorite social networking sites of the Saudi public, as it was found that 63% of the study sample follow the platform daily. 3- The majority of the study sample uses the Twitter platform as a source of information and search for it. 4- We conclude that the users of the Twitter platform have a great awareness of the many uses of Twitter, and came in first place to know the latest developments, the latest events and developments, and to follow up on the social changes occurring in Saudi women, as it helps them in forming public opinion on the issue of women assuming administrative positions. 5- One of the gratifications achieved by the study sample from their use of social networking sites is the formation of sufficient information about women assuming leadership positions, and participation in writing their opinions about women assuming leadership positions, and discussing with their friends. 6- The assumption of leadership positions by women does not contradict the values and customs of Saudi society from the viewpoint of the study sample. 7- Vision 2030 supported the issues that give women leadership positions.